Integrated dual-output optimization in hydroponics: Co-cultivation of Streptomyces thermocarboxydus-inoculated lettuce and Chlorella sp. microalgae for enhanced nutraceuticals and biofuel feedstock - Wasu Pathom-aree; Phinyarat Sensupa; Jeeraporn Pekkoh; Benyapa Kitwetch; Wageeporn Maneechote; Yupa Chromkaew; Benjamas Cheirsilp; Piroonporn Srimongkol; Kuan Shiong Khoo; Sirasit Srinuanpan (Journal of Applied Phycology, 2026)

An integrated waste-to-value bioprocess: Two-stage Limnospira (Spirulina) platensis cultivation in hydroponic effluent with second-stage light regulation for sustainable biomass valorization - Wageeporn Maneechote; Wasu Pathom-aree; Benjamas Cheirsilp; Piroonporn Srimongkol; Kuan Shiong Khoo; Sirasit Srinuanpan (Bioresource Technology Reports, 2026)

Microalgal Chlorella biomass and biorefinery residue-derived biochar combined with Actinobacteria: A biofertilizer strategy to enhance lettuce growth and rhizosphere microbial dynamics - Apiwit Kamngoen; Antira Wichaphian; Ratanaporn Kanyamee; Wasu Pathom-aree; Wassana Kamopas; Wageeporn Maneechote; Yupa Chromkaew; Kuan Shiong Khoo; Piroonporn Srimongkol; Benjamas Cheirsilp; Sirasit Srinuanpan (Algal Research, 2026)

Enhanced recovery of fluorescent pigment–protein complexes from Spirulina biomass via ultrasound-assisted deep eutectic solvent extraction: Toward sustainable natural food colorants with anti-colorectal cancer potential - Wageeporn Maneechote; Wasu Pathom-aree; Nakarin Suwannarach; Patcharin Chaijaem; Benjamas Cheirsilp; Supakit Chaipoot; Piroonporn Srimongkol; Shuhao Huo; Sirasit Srinuanpan (Food Bioscience, 2026)

Notes on the Description of Novel Prokaryotic Taxa - Wee Fei Aaron Teo; Juan A. Mondotte; Jia Liu; Hilal Ay; Marcelo Luiz Lima Brandão; Man Cai; Claudia Etchebehere; Wen-Jun Li; Wasu Pathom-aree; Tomoo Sawabe; Taegun Seo (Current Microbiology, 2026)

Innovative indoor hydroponic co-cultivation: Light-driven optimization of lettuce growth and microalgal Chlorella sp. G049 biomass with nutritional and biodiesel potentials - Jeeraporn Pekkoh; Kansinee Nuchtako; Wageeporn Maneechote; Apiwit Kamngoen; Antira Wichaphian; Wasu Pathom-aree; Yupa Chromkaew; Benjamas Cheirsilp; Kuan Shiong Khoo; Shuhao Huo; Piroonporn Srimongkol; Sirasit Srinuanpan (Algal Research, 2026)

Comparative evaluation of Chlorella biomass and its lipid-extracted residue: impacts on lettuce growth performance and rhizosphere microbial community - Antira Wichaphian; Apiwit Kamngoen; Wageeporn Maneechote; Wasu Pathom-aree; Tawanchai Khuendee; Yupa Chromkaew; Piroonporn Srimongkol; Benjamas Cheirsilp; Shuhao Huo; John Chi-Wei Lan; Kuan Shiong Khoo; Sirasit Srinuanpan (Journal of Applied Phycology, 2025)

Converting hydroponic effluent into high PUFA-rich biomass by mixotrophically cultivated microalga Chlorella sp. through light regulation for sustainable production of bioingredient and bioenergy - Nanthakrit Sriket; Antira Wichaphian; Apiwit Kamngoen; Jeeraporn Pekkoh; Wasu Pathom-aree; Yupa Chromkaew; Benjamas Cheirsilp; Wageeporn Maneechote; Yoong Kit Leong; Sirasit Srinuanpan (Journal of Environmental Chemical Engineering, 2025)

Optimizing the nutrient and light conditions for the enhancement of biomass and high value molecules productions in Spirulina using hydroponic effluent - A sustainable circular economy approach - Wageeporn Maneechote; Wasu Pathom-aree; Nanthakrit Sriket; Antira Wichaphian; Jeeraporn Pekkoh; Benjamas Cheirsilp; Sirasit Srinuanpan (Biomass and Bioenergy, 2025)

Hydroponic effluent recycling and resource recovery using heterotrophic Chlorella microalgae: Advancing a circular bioeconomy - Nanthakrit Sriket; Antira Wichaphian; Apiwit Kamngoen; Jeeraporn Pekkoh; Yupa Chromkaew; Wasu Pathom-aree; Wageeporn Maneechote; Benjamas Cheirsilp; Sirasit Srinuanpan (Journal of Water Process Engineering, 2024)

Zero-waste biorefining co-products from ultrasonically assisted deep eutectic solvent-pretreated Chlorella biomass: Sustainable production of biodiesel and bio-fertilizer - Antira Wichaphian; Nitiphong Kaewman; Wasu Pathom-aree; Kittiya Phinyo; Jeeraporn Pekkoh; Yupa Chromkaew; Benjamas Cheirsilp; Sirasit Srinuanpan (Bioresource Technology, 2024)

Atacama desert actinomycetes: taxonomic analysis, drought tolerance and plant growth promoting potential - Feiyang Xie; Barbara Andrews; Juan A. Asenjo; Michael Goodfellow; Wasu Pathom-aree (World Journal of Microbiology and Biotechnology, 2024)

Bioprocess Improvement for fermentation of pigmented Thai glutinous rice-based functional beverage (Sato) with superior antioxidant properties - Benjamas Cheirsilp; Jareeya Satansat; Kannika Wanthong; Radacha Chaiyasain; Jaruporn Rakmai; Nakarin Suwannarach; Jaturong Kumla; Wasu Pathom-aree; Guangce Wang; Sirasit Srinuanpan (Biocatalysis and Agricultural Biotechnology, 2023)

Turning waste CO2 into value-added biorefinery co-products using cyanobacterium Leptolyngbya sp. KC45 as a highly efficient living photocatalyst - Jeeraporn Pekkoh; Kritsana Duangjan; Kittiya Phinyo; Thida Kaewkod; Khomsan Ruangrit; Theera Thurakit; Chayakorn Pumas; Wasu Pathom-aree; Benjamas Cheirsilp; Wenhui Gu; Guangce Wang; Chatchawan Chaichana; et al. (Chemical Engineering Journal, 2023)

Application of phycocyanin from Arthrospira (Spirulina) platensis as a hair dye - Oranit Kraseasintra; Yingmanee Tragoolpua; Hataichanok Pandith; Ruttiros Khonkarn; Wasu Pathom-aree; Jeeraporn Pekkoh; Chayakorn Pumas (Frontiers in Marine Science, 2022)
Almost all of the current hair dye products today contain synthetic chemicals which may cause allergic reactions in some users. Phycocyanin (PC), a non-toxic cyanobacterial pigment, has been used in the food and cosmetics sectors. There are however, been a few reports on the application of phycocyanin as a hair colorant. This study aimed to assess the biological qualities of phycocyanin for use in natural hair dye product. Phycocyanin was tested for use against anti skin-pathogen ( Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 14990, Methicillin-resistant Staphylococcus aureus (MRSA) DMST 20625, Propionibacterium acnes DMST 14916, Candida albicans DMST 21424, and Malassezia furfur M21), cytotoxicity of human immortalized keratinocyte (HaCaT) cells and tested for color fastness when used as a shampoo wash. According to the findings, Arthrospira (Spirulina) platensis phycocyanin has not shown the potential for use against anti-skin pathogenic microorganisms. While testing phycocyanin at the maximum doses of 2.5 mg/mL, the cytotoxicity test revealed that it is not hazardous to HaCaT cells. Bleached hair was dyed with a mixture of phycocyanin, natural developers, and mordants. A chroma meter was used to monitor color changes after shampoo washing. The findings revealed that phycocyanin has dyeability potential. 50% of the dyed hair color remained after 5 shampoo washes. The stability and color degradation of phycocyanin in hair dye powder formulation demonstrated good physical stability along with four cycles of heating/cooling. As a result, we can see that this pigment has the potential to be used as an active ingredient in natural hair dyes.

Amycolatopsis vastitatis sp. nov., an isolate from a high altitude subsurface soil on Cerro Chajnantor, northern Chile - Hamidah Idris; Imen Nouioui; Wasu Pathom-aree; Jean Franco Castro; Alan T. Bull; Barbara A. Andrews; Juan A. Asenjo; Michael Goodfellow (Antonie van Leeuwenhoek, 2018)

Isolation and screening of biopolymer-degrading microorganisms from northern Thailand - Watsana Penkhrue; Chartchai Khanongnuch; Kazuo Masaki; Wasu Pathom-aree; Winita Punyodom; Saisamorn Lumyong (World Journal of Microbiology and Biotechnology, 2015)

Streptomyces ferrugineus sp. nov., isolated from mangrove soil in Thailand - Chang-ying Ruan; Li Zhang; Wan-wan Ye; Xiu-chao Xie; Rattanaporn Srivibool; Kannika Duangmal; Wasu Pathom-aree; Zi-xin Deng; Kui Hong (Antonie van Leeuwenhoek, 2015)

Isolation of rhizospheric and roots endophytic actinomycetes from Leguminosae plant and their activities to inhibit soybean pathogen, Xanthomonas campestris pv. glycine - Ratchanee Mingma; Wasu Pathom-aree; Savitr Trakulnaleamsai; Arinthip Thamchaipenet; Kannika Duangmal (World Journal of Microbiology and Biotechnology, 2014)

Verrucosispora fiedleri sp. nov., an actinomycete isolated from a fjord sediment which synthesizes proximicins - Michael Goodfellow; Roselyn Brown; Lina Ahmed; Wasu Pathom-aree; Alan T. Bull; Amanda L. Jones; James E. M. Stach; Tiago Domingues Zucchi; Lixin Zhang; Jian Wang (Antonie van Leeuwenhoek, 2013)

Diversity of actinomycetes isolated from Challenger Deep sediment (10,898 m) from the Mariana Trench - Wasu Pathom-aree; James E. M. Stach; Alan C. Ward; Koki Horikoshi; Alan T. Bull; Michael Goodfellow (Extremophiles, 2006)

Diversity of cultivable actinobacteria in geographically widespread marine sediments - Luis A. Maldonado; James E.M. Stach; Wasu Pathom-aree; Alan C. Ward; Alan T. Bull; Michael Goodfellow (Antonie van Leeuwenhoek, 2005)